Effect of Special Exercises on Psychological Endurance and Learning Basic Football Skills among Female Students - Ali Sabah Adday (Wahid Hasyim University, 2026)
Objectives: This study aimed to prepare special exercises designed to improve psychological endurance and support the learning of basic football skills among female students. It also examined the effect of these exercises on psychological endurance and selected football skills. Materials and Methods: The study used an experimental method with a pre-test and post-test design involving equivalent experimental and control groups. The sample consisted of 50 first-year female students from the College of Physical Education and Sports Sciences, University of Baghdad, selected from a population of 110 students. The participants were divided into an experimental group and a control group, with 25 students in each group. The experimental group received special exercises for eight weeks, with two educational units per week, while the control group followed the traditional teaching program. Psychological endurance and football skill tests, including passing, ball control, and dribbling, were administered before and after the intervention. Data were analyzed using means, standard deviations, and t-tests. Results: The results showed significant improvements in psychological endurance and basic football skills in both groups. However, the experimental group achieved greater improvement than the control group in all post-test variables. These findings indicate that the use of special exercises was more effective than traditional exercises in developing psychological endurance and improving football skill performance. Conclusions: Scientifically designed special exercises contributed positively to improving psychological endurance and learning basic football skills among female students. Integrating psychological preparation into football learning activities can increase confidence, motivation, active participation, and skill mastery.